Replicating the complexity of natural surfaces: technique validation and applications for biomimetics, ecology and evolution. (24th December 2018) - Kumar, Charchit; Palacios, Alejandro; Surapaneni, Venkata A.; Bold, Georg; Thielen, Marc; Licht, Erik; Higham, Timothy E.; Speck, Thomas; Le Houérou, Vincent
Abstract : The surfaces of animals, plants and abiotic structures are not only important for organismal survival, but they have also inspired countless biomimetic and industrial applications. Additionally, the surfaces of animals and plants exhibit an unprecedented level of diversity, and animals often move on the surface of plants. Replicating these surfaces offers a number of advantages, such as preserving a surface that is likely to degrade over time, controlling for non-structural aspects of surfaces, such as compliance and chemistry, and being able to produce large areas of a small surface. In this paper, we compare three replication techniques among a number of species of plants, a technical surface and a rock. We then use two model parameters (cross-covariance function ratio and relative topography difference) to develop a unique method for quantitatively evaluating the quality of the replication. Finally, we outline future directions that can employ highly accurate surface replications, including ecological and evolutionary studies, biomechanical experiments, industrial applications and improving haptic properties of bioinspired surfaces. The recent advances associated with surface replication and imaging technology have formed a foundation on which to incorporate surface information into biological sciences and to improve industrial and biomimetic applications. This article is part of the theme issue 'Bioinspired materials and surfaces for green science and technology'.